Funders: The missing link in equitable global health research? - Esmita Charani; Seye Abimbola; Madhukar Pai; Olusoji Adeyi; Marc Mendelson; Ramanan Laxminarayan; Muneera A. Rasheed (Public Library of Science (PLoS), 2022)
Global health research is mired by inequities, some of which are linked to current approaches to research funding. The role of funders and donors in achieving greater equity in global health research needs to be clearly defined. Imbalances of power and resources between high income countries (HICs) and low- and middle-income countries (LMICs) is such that many funding approaches do not centre the role of LMIC researchers in shaping global health research priorities and agenda. Relative to need, there is also disparity in financial investment by LMIC governments in health research. These imbalances put at a disadvantage LMIC health professionals and researchers who are at forefront of global health practice. Whilst many LMICs do not have the means (due to geopolitical, historical, and economic reasons) for direct investment, if those with means were to invest more of their own funds in health research, it may help LMICs become more self-sufficient and shift some of the power imbalances. Funders and donors in HICs should address inequities in their approach to research funding and proactively identify mechanisms that assure greater equity-including via direct funding to LMIC researchers and direct funding to build local LMIC-based, led, and run knowledge infrastructures. To collectively shape a new approach to global health research funding, it is essential that funders and donors are part of the conversation. This article provides a way to bring funders and donors into the conversation on equity in global health research.